2016
DOI: 10.1177/0301006616673850
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual Integration Delayed by Stimulus Onset Asynchrony Between Auditory and Visual Stimuli in Older Adults

Abstract: Although neuronal studies have shown that audiovisual integration is regulated by temporal factors, there is still little knowledge about the impact of temporal factors on audiovisual integration in older adults. To clarify how stimulus onset asynchrony (SOA) between auditory and visual stimuli modulates age-related audiovisual integration, 20 younger adults (21-24 years) and 20 older adults (61-80 years) were instructed to perform an auditory or visual stimuli discrimination experiment. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 40 publications
7
43
0
Order By: Relevance
“…Yet, studies have shown that although older adults exhibit in general worse performance as compared to their young counterparts (e.g., slower reaction times), they show greater multisensory gains for different sensory combinations, including audiovisual, visual‐somatosensory, and audio‐somatosensory stimulus pairs . The greater multisensory gains observed in older adults have been replicated in paradigms differing in terms of their attentional demands and the tasks employed, such as simple reaction, discrimination, saccadic reaction time, and temporal perception tasks, thus pointing to a robust age‐dependent facilitative effect of multisensory processing on behavioral performance.…”
Section: Multisensory Processing In Old Age: Current Statusmentioning
confidence: 99%
See 3 more Smart Citations
“…Yet, studies have shown that although older adults exhibit in general worse performance as compared to their young counterparts (e.g., slower reaction times), they show greater multisensory gains for different sensory combinations, including audiovisual, visual‐somatosensory, and audio‐somatosensory stimulus pairs . The greater multisensory gains observed in older adults have been replicated in paradigms differing in terms of their attentional demands and the tasks employed, such as simple reaction, discrimination, saccadic reaction time, and temporal perception tasks, thus pointing to a robust age‐dependent facilitative effect of multisensory processing on behavioral performance.…”
Section: Multisensory Processing In Old Age: Current Statusmentioning
confidence: 99%
“…Aging may also affect the temporal characteristics of multisensory integration, which has important implications for other cognitive and motor functions . Converging evidence shows a widening of the temporal window of audiovisual integration, presumably due to the slower and more variable peripheral sensory processing . The widening of the window is a double‐edged sword: it can allow for unifying irrelevant events, thereby rendering it difficult to discriminate simultaneity, temporal order, and causal relationships among sensory stimuli, but it can also increase the possibility of integrating sensory events that might not have been integrated given the general age‐related slowing in sensory processing.…”
Section: Multisensory Processing In Old Age: Current Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…Among multisensory integration modalities, the most typical is audiovisual integration in humans and animals, which has been represented in several previous studies ( Molholm et al, 2002 , 2006 ; Roach et al, 2006 ; Doehrmann and Naumer, 2008 ). Recently, our event-related potential (ERP) studies have indicated that audiovisual integration is regulated by temporal factors ( Yang et al, 2014 ; Ren et al, 2017b ). The temporal structure of auditory and visual stimuli can intervene in human audiovisual processing.…”
Section: Introductionmentioning
confidence: 99%